Living with retinitis pigmentosa: Visual perceptual difficultie - Chacón-López, Helena; López-Justicia, M. Dolores (Journal of Exceptional People, 2016)
The aim of this study was to determine the state of the visual perception of 26 people with RP and 31 without visual impairment, using the TVPS (Test of Visual Perceptual Skills), as well as to find out the subtests on which those aff ected by RP have more difficulties and those on which they have less. Another aim of the study was to determine the relationship between Near Visual Acuity (NVA), Visual Field (VF) and visual perceptive performance. The results showed diff erences in all subtests between both groups. A descriptive analysis showed that those aff ected by RP have greater difficulty on Form Constancy and on Figure Ground and least on Visual Memory subtests. Significant correlations were found between NVA (Spatial Relations and Figure Ground subtests), VF (Visual Constancy and Figure Ground subtests) and visual perceptive performance. It was concluded that the findings of the study have important implications in planning interventions and in designing training programs for activities of daily life, of movement, recreation and social life, since visual perception affects these activities, and in the technological or computerized development of assistance aimed at improving the use of residual vision.
Keywords: testy zrakového pole; Young Adult; zraková pole; zrakové testy; Male; zraková ostrost; Visual Fields; mladý dospělý; Vision Tests; Adult; Case-Control Studies; dospělí; mužské pohlaví; Visual Field Tests; Visual Acuity; lidé; ženské pohlaví; studie případů a kontrol; Humans; Retinitis Pigmentosa; Female; lidé středního věku; Visual Perception; retinopathia pigmentosa; Middle Aged; zraková percepce